The breeding behaviour, advertisement call and tadpole of Limnonectes dabanus (Anura: Dicroglossidae) - Rowley, Jodi J. L.; Le, Duong Thi Thuy; Hoang, Huy Duc; Altig, Ronald (Zootaxa, 2014)
Fanged frogs (Limnonectes) are a group of dicroglossid frogs from Asia that often have reversed sexual dimorphism with larger males. Limnonectes dabanus is a poorly known species of fanged frog from forested habitats in southern Vietnam and eastern Cambodia. Adult males exhibit an extreme degree of megacephaly and possess bizarre head ornamentation. L. dabanus breeds in shallow, non-flowing or very slow-flowing pools, puddles, and drainage ditches. Eggs are laid as a widely spaced array, and the larvae have a morphology typical of pond-dwelling tadpoles. Although males of the species lack vocal sacs, they produce a low-pitched (0.4–0.6 kHz), single-note advertisement call that sounds like a drop of water falling into water. Given the spacing of calling males, presence of multiple females near breeding sites, and reversed sexual dimorphism, the mating system of L. dabanus may be an example of resource-defense polygyny, and the massive head of the male is likely used in male combat.